Proust as philosopher : the art of metaphor - Beistegui, Miguel de, 1966- (Routledge, 2013)
Marcel Proust's In Search of Lost Time has long fascinated philosophers for its complex accounts of time, personal identity and narrative, amongst many other themes. Proust as Philosopher: The Art of Metaphor is the first book to try and connect Proust's implicit ontology of experience with the question of style, and of metaphor in particular.Miguel de Beistegui begins with an observation: throughout In Search of Lost Time, the two main characters seem prone to chronic dissatisfaction in matters of love, friendship and even art. Reality always falls short.